TRANSMISI KEBIJAKAN MONETER MELALUI JALUR PERUMAHAN - Utama, Chandra (Faculty of Economics and Business, University of Muhammadiyah Malang, 2012)
After the subprime mortgage crisis in the USA, the housing market hasbecome more concerned in the monetary policy makers. The housing developers must understand the role of the housing sector in the monetary transmission mechanism to find the goal, price stability, and sustainable employment as well as economic growth. This paper proposes another channel, the housing sectors; as the 6 th channel that transmit monetary policy. It focuses to the direct and indirect sub-channel of housing to the economyand analyzes the role of housing in the monetary transmission mechanism.